Penerapan Model Experiential Learning Berbantuan Media Gambar Untuk Meningkatkan Kreativitas Kerajinan Tangan Peserta Didik - Aris Abdul Rohman; Ace Iwan Suryawan; Imam Jahrudin Priyanto (EDUCARE, 2019)
The title of this research is the application of experiential learning models assisted by picture media to enhance the creativity of students' handicrafts. The problem under study is about the results of students' creativity using the experiential learning model assisted by the image media. This research aims to determine the results of the creativity of handicrafts in arts and culture lessons and crafts using experiential learning models. The theory used in this study is David Kolb (1984) for the experiential learning model and Utami Munandar (2012) for creativity. This research is quantitative. The population in this study was 28 people for the control class and 28 people for the experimental class. Data collection techniques used were observation, and practice tests. Data collection instruments consisted of observation sheets and practice test assessment rubrics. The results of this study indicate that there is a difference in the increase in the results of the creativity of handicrafts aided by media images.